Effectiveness of advanced cardiovascular life support in hyperkalemic cardiac arrest: A randomized experimental study in pigs - Najmiddin Mamadjonov; Wan Young Heo; Kyung Woon Jeung; Yong Hun Jung; Hyoung Youn Lee; Seok Jin Ryu; Byung Kook Lee; Yong Soo Cho; Tag Heo (Heliyon)
Current treatment recommendations for hyperkalemic cardiac arrest focus exclusively on the addition of antihyperkalemic therapies and are otherwise identical to those for cardiac arrest caused by non-hyperkalemic etiologies. We were unable to find any studies that specifically examine the hemodynamic effects of cardiopulmonary resuscitation in hyperkalemic cardiac arrest compared to cardiac arrest from non-hyperkalemic etiologies. We hypothesized that myocardial ischemic contracture would be less severe in hyperkalemic cardiac arrest compared with ventricular fibrillation cardiac arrest, resulting in higher cerebral perfusion pressure, brain tissue oxygen tension, and coronary perfusion pressure during cardiopulmonary resuscitation. Twenty-two pigs randomly underwent either electrically induced ventricular fibrillation arrest or hyperkalemic arrest induced by potassium infusion. Hemodynamic, echocardiographic, and brain tissue oxygen tension measurements were obtained during advanced cardiovascular life support and compared using linear mixed-effects models. Two animals developed massive hemothorax associated with cardiopulmonary resuscitation and were excluded from further analysis. The remaining 20 animals had no internal organ injury due to cardiopulmonary resuscitation and were included in the study. Left ventricular wall thickness was significantly lower in the hyperkalemic arrest group than in the ventricular fibrillation arrest group (group effect, P = 0.019). The decrease in end-diastolic volume over time was significantly less pronounced in the hyperkalemic arrest group (group-time interaction, P = 0.010). Coronary perfusion pressure (group effect, P = 0.041) and cerebral perfusion pressure (group effect, P = 0.020) were significantly lower in the hyperkalemic arrest group. Although not significant, brain tissue oxygen tension was also lower in the hyperkalemic arrest group. In conclusion, the left ventricular wall thickness was smaller, and the decrease in end-diastolic volume over time was less pronounced in the hyperkalemic arrest group. However, perfusion pressure was poorer, and cerebral oxygenation was not better in the hyperkalemic arrest group.